Influence of 2-hydroxy-4-(Methylthio)butanoic Acid on Early Egg and Chick Weights of Broiler Breeders - Lien, R.J.; Hess, J.B.; Giesen, A.F.; Yersin, A.G. (International Journal of Poultry Science, 2003)
This trial was conducted to determine if early egg and chick weights of broiler breeders are increased by dietary 2-hydroxy-4-(methylthio)butanoic acid (HMB) supplementation. Hens of two strains were provided feed with HMB levels equivalent to 0, 0.5, 1 and 1.5 kg methionine/tonne from 21 to 35 wk. Chick yield (chick weight/egg weight) increased significantly as dietary HMB level was increased from 0 to 1 kg/tonne; however, egg and chick weights were not individually affected by increasing HMB level. Egg production was increased from 29 to 35 wk by the 0.5 kg/tonne treatment; however, there was neither improvement prior to this period nor further increases due to greater HMB levels. Mortality, primarily due to fatty-liver hemorrhagic syndrome, was markedly elevated at low HMB levels in one strain. Although increasing HMB levels had some affect on chick yield, results were not as evident as what has been measured in commercial layers.